2009
DOI: 10.1088/0953-8984/21/13/134009
|View full text |Cite
|
Sign up to set email alerts
|

O- and H-induced surface core level shifts on Ru(0001): prevalence of the additivity rule

Abstract: In previous work on adsorbate-induced surface core level shifts (SCLSs), the effects caused by O atom adsorption on Rh(111) and Ru(0001) were found to be additive: the measured shifts for first layer Ru atoms depended linearly on the number of directly coordinated O atoms. Densityfunctional theory calculations quantitatively reproduced this effect, allowed separation of initial and final state contributions, and provided an explanation in terms of a roughly constant charge transfer per O atom. We have now cond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
6
6
0
Order By: Relevance
“…Very recently we have completed theoretical work on these systems [26] which resulted in excellent quantitative agreement with the present results in terms of geometrical and other parameters, corroborating our results and in particular the conclusions about the visibility of H atoms for quantitative LEED.…”
Section: Note Added In Proofsupporting
confidence: 90%
See 1 more Smart Citation
“…Very recently we have completed theoretical work on these systems [26] which resulted in excellent quantitative agreement with the present results in terms of geometrical and other parameters, corroborating our results and in particular the conclusions about the visibility of H atoms for quantitative LEED.…”
Section: Note Added In Proofsupporting
confidence: 90%
“…Notably, the latter is one monolayer for the sum of O and H atoms in the O + 3H layer. Calculations have shown that the preference of H for fcc over hcp sites in the pure H-layer is only about 2.6% for monolayer coverage [26]. For the dilute (O + H) layer these arguments do not apply; there is ample space, and so the H reverts to its preferred fcc site.…”
Section: Geometry Parametersmentioning
confidence: 99%
“…4 (1-6) indicate that the major part of the Ru remains metallic (Ru 0 ) according to component 2. We also observe that below 50 % of Ru molar ratio, we have three additional components at high binding energy [42][43][44][45] corresponding to the Ru 4+ (peak 3), Ru 6+ (peak 4) and Ru 8+ (peak 5), respectively. Clean surface contribution (unsaturated as dangling bonds) corresponding to peak 1 is also observed in these latter samples.…”
Section: Resultsmentioning
confidence: 63%
“…Figure 5 provides an analytical description about electron exchange processes that occur from one metal to the other and the charge transferred between a metal and a reactant. We also provide details on how the exchange of electrons can be related to the chemisorption TABLE I: Experimentally determined core level binding energy and components for Pd 3d 5/2 and Ru 3p 3/2 from Pd X Ru 1−X (X : 0, 0.1, 0.3, 0.5, 0.7, 0.9 and 1) NPs [35,[40][41][42][43][44][45]. process and catalytic activity of NPs.…”
Section: Resultsmentioning
confidence: 99%
“…The SCLS is calculated for an atom coordinated to one (θ = 0.25) and two (θ = 0.5) adsorbates. In previous studies considering some specific systems [16,27,43], it has been reported that the SCLSs scale linearly with surface coverage. The present results generally support this view concerning the reducing adsorbates H and CO.…”
Section: Coverage Dependencementioning
confidence: 96%